Supply Infrastructure Financing & Kualitas Mutu Layanan dalam Meningkatkan Kepuasan Peserta JKN - Zirma Julianda; Ecep Mochammad Holiqurrahman (Jurnal Jaminan Kesehatan Nasional, 2023)
BPJS Kesehatan as the National Health Insurance Institutions needs to understand participant satisfaction to this is important to build public trust in the implementation of the National Health Insurance. Participant satisfaction is an indicator of the quality of health services that is measured and compared between expected services and services perceived. The quality of service depends on the ability of the service provider to consistently meet the expectations of participants. Participants' demands for service quality are not only related to physical healing of illnesses but also regarding customer satisfaction with attitudes, knowledge, skills of officers providing services, communication, availability of information, adequate facilities and physical environment. Health Facilities strive to continue developing infrastructure, working capital, complete facilities and infrastructure, as well as expanding service points in order to increase Health Facilities commitment in maintaining the quality of service to JKN-KIS participants. Based on the 2021 Participant Satisfaction Survey,satisfaction indicators of participants through Health Services include facilities and infrastructure, waiting room and chairs, completeness of medical devices and sophisticated equipment, Health Facilities accessible. This is the basis for BPJS Kesehatan to collaborate with Partner Banks to provide Supply Infrastructure Financing (SIF) to Health Facilities (partner) that require business development funds. The purpose of this research is to evaluate that health services in health facilities are related to the satisfaction of JKN participants. the results of the literacy review of previous researchers and the evaluation of the SIF realization, the authors conclude that JKN participant satisfaction is influenced by health facility services.